Efek Pemberian Pupuk Kascing Dan Urea Terhadap Pertumbuhan Bibit Gaharu (Aquilaria malaccensis Lamk.) - Mokhamad Saiful Anwar; Wardati Wardati; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the interaction of vermicompost and urea and get the best treatment to increase the growth of the gaharu seedlings (Aquillaria malaccensis Lamk.). The research was conducted in experimental station of Agriculture Faculty, University of Riau, from September to November 2016. This research uses Completely Randomized Design, which consists of two factors and three replications. The first factor was the dosage of vermicompost (K) consisting of 4 level: 0 g/ polybag, 100 g / polybag, 200 g/ polybag, and 300 g/ polybag; And the second factor is the dose of urea fertilizer (U) consisting of 4 levels: 0 g/ polybag, 0.5 g/ polybag, 1 g/ polybag, and 2 g/ polybag. Each experimental unit consists of 2 seedlings so that there are 96 gaharu seedlings. Data were analyzed The observation result of each parameter was statistically analyzed by using vocabulary and tested using DNMRT (Duncan's New Multiple Range Test) at 5% level. The parameters observed were plant height, number of leaves, stem diameter, leaf area, shoots and root ratio, and dry weight. The interaction of kascing 300 g/ polybag and urea dosage 2 g/ polybag gave the best effect to the parameters of gaharu seedlings height accretion, the accretion of leaf number, the accretion of stem diameter, leaf area and dry weight Keywords: Vermicompost, urea fertilizer, gaharu seedlings